Regenerative engineering of musculoskeletal tissues and interfaces - Nukavarapu, Syam P.; Freeman, Joseph; Laurencin, Cato T. (Woodhead Publishing series in biomaterials, 2015)
Repair and regeneration of musculoskeletal tissues is generating substantial interest within the biomedical community. Consequently, these are the most researched tissues from the regeneration point of view. Regenerative Engineering of Musculoskeletal Tissues and Interfaces presents information on the fundamentals, progress and recent developments related to the repair and regeneration of musculoskeletal tissues and interfaces. This comprehensive review looks at individual tissues as well as tissue interfaces. Early chapters cover various fundamentals of biomaterials and scaffolds, types of c.